1205. Emergence of Carbapenemase Producing Enterobacteriaceae in South Central Ontario, Canada. (26th November 2018) - Zhong, Zoe; Faheem, Amna; Farooqi, Lubna; Armstrong, Irene; Borgundvaag, Emily; Coleman, Brenda; Green, Karen; Jayasinghe, Kithsiri; Johnstone, Jennie; Katz, Kevin; Kohler, Philipp; Li, Angel; et al.
Abstract: Background: The spread of CPE is an increasing global threat to patient safety. We describe the introduction and evolution of CPE in south-central Ontario, Canada. Methods: The Toronto Invasive Bacterial Diseases Network has performed population based surveillance for CPE in metropolitan Toronto and Peel region from first identified isolates in 2007. All laboratories test/refer all carbapenem non-susceptible Enterobacterial isolates for PCR testing for carbapenemases. Demographic and medical data and travel history are collected from chart review and patient/physician interview. Results: Since 2007, 659 patients have been identified as colonized/infected with CPE; 362, 57%) have at least one clinical isolate. Annual incidence has increased from 0 in 2006 to 1.3 per 100, 000 in 2016/17 (Figure 1). First bacteremia occurred in 2010, the incidence in 2017 was 0.14 per 100, 000 population. 388 (59%) patients were male, median age was 70 years (range 3 months–100 years). Most common genes among first isolates were NDM (306, 46%), OX48 (149, 23%), KPC (122, 19%). Most common species were K. pneumoniae (268, 41%) and E. coli (259, 39%). Over time, second species/same gene were identified in 113 (16%) patients. In addition, 34/xxx patients with isolates with NDM and/or OXA-48 subsequently had a second isolate with a different gene/gene combination. Of 518 patients whose travel and hospitalization history are available, patients with VIM were less likely than other patients to have a foreign hospitalization or travel history (9/28 vs. 341/490, P < 0.0001). Patients with KPC were more likely to have a hospitalization history outside Canada and the Indian subcontinent (25/70, 36%), in Canada (47/164, 29%) than to have no hospitalization in the last year (13/93, 14%), or a history of hospitalization in the Indian subcontinent (2/191, 1%) ( P < 0.001). The number of incident patients with different hospitalization and travel history over time is shown in Figure 2. Conclusion: CPE is increasingly recognized in southern Ontario, both in patients with a history of exposure in healthcare in other countries, and to healthcare in Canada. Intensification of control programs is urgently needed. Disclosures: S. Poutanen, MERCK: Scientific Advisor, Speaker honorarium. COPAN: Speaker(but not part of a bureau), Travel reimbursement. Accelerate Diagnostics: Investigator, Research support. Bio-Rad: Investigator, Research support. bioMérieux: Investigator, Research support.